Entrepreneurial education in basic education: identifying challenges from a bibliometric analysis and systematic review - Carvalho, Agair Juliete Cavalcante; Corrêa, Rubia Oliveira; Carvalho, Gustavo Dambiski Gomes de; Olave, Maria Elena Leon (REGEPE Entrepreneurship and Small Business Journal, 2022)
Objective: to analyze, in the Web of Science database, the scientific production on the theme "entrepreneurial education", in order to observe the literature panorama and the challenges inherent to the performance of entrepreneurship in Basic Education. Methodology: the study was divided into two parts: (1) analysis, through the bibliometrics technique, of the indicators related to the type of document, the authors and their nationality, and the number of citations; and (2) conducting a systematic, post-application review of the Proknow-C method. Main results: the number of studies with this educational approach is low and, in general, isolated cases are analyzed. The literature panorama reaffirms the thematic complexity and highlights two major and main challenges – school management and teacher preparation. Theoretical/methodological contributions: through the presented literary portfolio, it is possible to identify the complexity and heterogeneity of the challenges linked to the application of the entrepreneurial approach in Basic Education teaching institutions. Relevance/originality: this study exposes the development of research on entrepreneurship education in basic education, as well as the challenges associated with the implementation and development of this educational approach. Social/management contributions: the results of the study demonstrated the need for integration between the political, business, educational, family spheres and the support of society in general for the implementation and development of entrepreneurship in Basic Education.